Socialization of Sustainable Crab Fishing Methods in Fanamo and Omawita Villages, Far East Mimika District - Ida Ayu Purba Riani; Transna Putra Urip; Yundy Hafizrianda; Agustina Ester Antoh; Pisi Bethania Titalessy (Jurnal Indonesia Sosial Sains, 2026)
Mangrove crab (Scylla spp.) fisheries constitute an important livelihood source for coastal communities in Far East Mimika District, Indonesia. However, increasing market demand has led to unsustainable fishing practices, including the capture of egg-bearing females, harvesting of undersized crabs, and the use of nonselective fishing gear that damages mangrove habitats. These practices threaten crab stock sustainability and the long-term welfare of fishing communities. This study aims to evaluate the implementation of a socialization and training program promoting sustainable mangrove crab fishing methods in Fanamo and Omawita Villages. The program applied a community-based approach consisting of awareness campaigns, hands-on training in eco-friendly fishing gear (folding traps with escape gaps and selective gillnets), introduction of minimum catch-size regulations, establishment of no-catch zones, and implementation of a simple catch logbook system. The activities were conducted through participatory discussions, field demonstrations, workshops, and mentoring. The results indicate increased awareness among fishermen regarding conservation principles, adoption of environmentally friendly fishing gear by participating fishers, and initial use of catch logbooks for monitoring productivity. Despite challenges such as limited literacy and time constraints, the mentoring approach strengthened behavioral change and local acceptance of sustainable practices. The study concludes that integrating socialization, technical training, and community-based monitoring effectively supports sustainable resource management while maintaining fishers’ productivity. This initiative provides a practical model for strengthening coastal governance and ensuring the ecological and economic sustainability of mangrove crab fisheries.